Research on the technological development of aluminum alloy carbodies for metro trains in China - SU Ke; SU Yongzhang; LIU Yongqiang; YUE Yixin; LIANG Jinfa; WANG Yubing (机车电传动)
Aluminum alloy carbody technology for metro trains in China has developed through four stages: technology introduction, localization breakthrough, enterprise-level independent innovation, and national-level collaborative innovation. With the establishment of the Chinese standard metro train technology platform, China has achieved a leap forward from dependence on imports to the independent development of autonomous and controllable products. This paper presents a systematic review of China’s development journey in aluminum alloy carbody technology for metro trains, using the technology platform for the fourth-generation B-type cars developed by CRRC ZELC as a case study. It clarifies the technological evolution patterns and driving mechanisms throughout this process. The study shows that technological iterations have been synergistically driven by technological innovations, market demands, cost optimization, and policy guidance. Looking ahead, the technology in this field is anticipated to undergo in-depth development towards modularization, sustainability, and intelligence throughout the full life cycle of products, thereby enhancing China's international competitiveness in the rail transit equipment sector.